Cryogels: recent applications in 3D-bioprinting, injectable cryogels, drug delivery, and wound healing - Jones, Luke O.; Williams, Leah; Boam, Tasmin; Kalmet, Martin; Oguike, Chidubem; Hatton, Fiona L. (Beilstein Journal of Organic Chemistry, 2021)
Cryogels are macroporous polymeric structures formed from the cryogelation of monomers/polymers in a solvent below freezing temperature. Due to their inherent interconnected macroporosity, ease of preparation, and biocompatibility, they are increasingly being investigated for use in biomedical applications such as 3D-bioprinting, drug delivery, wound healing, and as injectable therapeutics. This review highlights the fundamentals of macroporous cryogel preparation, cryogel properties that can be useful in the highlighted biomedical applications, followed by a comprehensive review of recent studies in these areas. Research evaluated includes the use of cryogels to combat various types of cancer, for implantation without surgical incision, and use as highly effective wound dressings. Furthermore, conclusions and outlooks are discussed for the use of these promising and durable macroporous cryogels.
Keywords: 3D-bioprinting; cryogels; drug delivery; injectable cryogel; macroporous hydrogel; wound healing